No-scalpel vasectomy in the National Hospital Cayetano Heredia. - Mauricio, Juan (2015)
Retrospective study of the first 70 ambulatory scalpelless vasectomies performed at the Planned Parenthood Clinic of Cayetano Heredia National Hospital from january 1992 through August 1994. Age, education, number of children of patients and information source, time between decision and performance of the operation, and surgical technique are described. Surgery duration was 23 minutes and postoperative morbidity was 7 %.